HUBUNGAN PRESTASI BELAJAR MICRO TEACHING DAN MAGANG KEPENDIDIKAN 3 DENGAN KESIAPAN MAHASISWA MENJADI GURU - Endraningsih, Hesti Tri; Akhyar, Muhammad; Rohman, Ngatao (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
This study aims at examining the effect of (1) micro teaching’s achievement on readiness to become a teacher in Mechanical Engineering Education Students class of 2014 (2) learning achievement of educational internship 3 on the readiness to become a teacher in Mechanical Engineering Education Students class of 2014 (3) the achievement of micro teaching and education internship 3 jointly on the readiness to become a teacher in Mechanical Engineering Education Students class of 2014.This research is correlational research. The population in this study were all of Mechanical Engineering Education Students class of 2014, and there are 65 students to be population. The sample size taken by simple random sampling technique, and its taken 55 students. Data collection was carried out with documentation for micro teaching’s achievement and educational internship 3, and questionnaire method for teacher readiness data. The trial instrument of readiness to become a teacher was carried out in Civil Engineering Education Students class of 2014 in 30 students.. Data analysis techniques using partial correlation and multiple linear regression. Testing and analyzing data using SPPS software version 21.0. The results show that (1) there is a significant positive relationship between micro teaching’s achievement with the readiness to become a teacher in Mechanical Engineering Education Students class of 2014; (2) there is a significant positive relationship between the achievement of educational internship 3 and the readiness to become a teacher in Mechanical Engineering Education Students class of 2014; (3) there is a significant positive relationship between the achievement of learning micro teaching and education internship 3 with the readiness to become a teacher for Mechanical Engineering Education Students class of 2014.